Factors Influencing Intention and Behaviour of Agricultural Extension Staff Concerting Post-Covid-19 Digital Technical Guidance: A Study in Yogyakarta, Indonesia - Kaliky, Rahima; Juniarti, Hafni Amalia; Kusumawati, Septi (Research in Social Sciences and Technology, 2023)
Agriculture extension staffs are encouraged to attempt more efficient methods to enhance their competency through digital webinars or technical guidance, in Bahasa Bimbingan Teknis (Bimtek) programs. The research aims to explore factors influencing the intention and behavior of agricultural extension staff towards the Technical guidance online Ministry of Agriculture in Special Region Yogyakarta, Indonesia. This research included the Behavior Intention (BI) and Use Behavior (UB) models with significant construct. The research used the quantitative method and analyzed PLS-SEM. One hundred eighty extension staffs participated, chiefly 34-42 years old. All of the indicators passed the outer model assessment. The analysis results conclude that significant effects are Attitude to BI, Control Behavior to BI, Perceived Usefulness to BI, and Behavior Intention to UB. The perception of extension staffs about Technical guidance online can enhance their performance to continue using it in obtaining agricultural technology information, extension materials, information on agricultural policies, and the latest agricultural development programs. The insignificant constructs are Subjective Norm, Motivation, and Perceived Ease to Use. The validated research model explains 61% of the variance (R2 = 0.61) in Attitude, Perceived Usefulness, and Control Behaviour towards Behavior Intention (BI). Moreover, BI explains 8.9% of the variance (R2 = 0.089) in UB of Technical guidance online. This research found that BI and UB have Q2 values of 0.538 and 0.077. The practical implication could be applied as preliminary development planning studies to enhance the efficiency of Technical guidance online as Bank Data.